Pembuatan Sistem Analisis Kualitas Air Limbah Sisa Industri Secara Online Menggunakan Software Reliance SCADA, Framework .Net Core dan PostgresSQL - Putra, Firmansyah Adi; Noviana, Rina; Suroso, Amat (Politeknik Harapan Bersama, 2021)
The government through the Ministry of Environment and Forestry (KLHK) has created several flagship programs such as “PROPER” and “SPARING” which function as supervision and aim to encourage industry to comply with environmental regulations. In this program, industry players who fall into the predetermined criteria are required to report their industrial waste water online to the Ministry of Environment and Forestry. Perusahaan Gas Negara through its subsidiary PGN Solution is always obedient to report the remaining industrial waste to the Ministry of Environment and Forestry. However, the results of this report cannot be immediately known whether the results are good or not, this is because KLHK will only release and display the results of the analysis and reporting to its online system after some time.In order to immediately know the results of the analysis without having to wait for the results of the release from the Ministry of Environment and Forestry, we need a system that can store the data directly on the database server without interrupting the data which is also sent directly to the Ministry of Environment and Forestry. Making this system using the Waterfall method, C# language, Net Core Framework and PostgreSQL as a database and Reliance SCADA software as a medium for data retrieval. The implementation of this system will facilitate the analysis and decision-making process if residual waste data is found whose results may not be as good according to KLHK standards